EFL Teacher’s Challenges in Implementing Project Based Learning (PjBL) in the Context of Merdeka Curriculum at Vocational High School - Nurfitrah Awaliyah; Syarifuddin Dollah; Muh. Tahir; Nurrahma Maulida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to explore the challenges faced by English teacher in implementing Project-Based Learning (PjBL) in the context of the Merdeka Curriculum in Vocational High Schools (SMK). Using descriptive qualitative method, data was collected through non participant observation conducted three times and fifteen minutes of semi-structural interviews with an EFL teacher at SMKN 5 Pangkep. The findings reveal that teacher encountered various obstacles, such as limited class hours, students' lack of understanding of project concepts, and insufficient opportunities for professional development. These findings highlight the need for ongoing support, whether in the form of training or policy adjustments, to ensure that PjBL implementation can be carried out more effectively in line with the spirit of the Merdeka Curriculum.